Student pharmacist practice-based interprofessional education in Scotland: a qualitative study of stakeholders' views and experiences. Issue 1 (2nd January 2023) - Jebara, Tesnime; Power, Ailsa; Boyter, Anne; A. Jacob, Sabrina; Portlock, Jane; Cunningham, Scott
ABSTRACT: Scottish Government funding supports practice-based experiential learning (EL) for student pharmacists. We explored views and experiences of key stakeholders on current practice and future development of interprofessional education (IPE) in EL including barriers and enablers. A pre-piloted schedule was used for online qualitative semi-structured interviews. eMail invitations were sent to 37 stakeholders with an information sheet and consent process. Interviews were analyzed thematically by two researchers independently. Recruitment continued until data saturation and wide representation were achieved. Twenty interviews were conducted with eight EL facilitators, seven faculty and five policy stakeholders. "Nature and experience of current IPE in EL activities" and "Future developments" were the two main themes. Barriers and enablers were also identified at macro, meso, and micro socio-institutional levels. The essence of the analysis highlighted stakeholders' views of the importance of building on current IPE while challenging the ethos and culture of EL practices. All stakeholders should be involved in co-production, training, piloting, and evaluation of curricular developments to overcome logistic barriers and enhanced enablers. Finally, the importance of workload management strategies and continuity of funding for success was also stressed by those interviewed. Future research could include designing frameworks for developing and implementing IPE within EL.